Six Reasons why the Problem of Soil Pollution Cannot Be Ignored - Khudargonovich, Yuldashov Murod; Murodovna, Yuldashova Mokhina; qizi, Turobova Sadoqat Orif (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article we will talk about the situation that arose as a result of inadequate human attitude to nature and natural resources, that is, about the possible negative consequences of the state of soil pollution for the environment.